Assessment of Water Quality of Shkumbini River, Albania - Paparisto, Anila; Lazo, Pranvera; Halimi, Eltjon; Duka, Sonila; Hamzaraj, Etleva; Laknori, Odeta; Pepa, Bledar (Asian Journal of Chemistry, 2010)
Albania is rich in water resources including lakes, rivers, spring water, lagoons and sea, with a considerable quantity of available water. Water quality monitoring of Shkumbini river (181 km long) was carried out based on the investigation of two different parameters: biological parameters based on some insect and insecticide colonies, used as bio-indicators and chemical-physical parameters of the water of the river. Two different stations positioned along the river segment paper-peqin, was selected as the object of present study. EPT-Biotic index and biotic index of family/sequence level, as well as biotic index parameter [Stroud water research center] was used for water quality bioclassification more than 17 families [Ephemerelidae, Baetidae, Hydropsychidae, Simuliidae, Cerapotogonidae, Gomphidae, Corduliidae, Cordulegasteridae, etc.] dominated by species of Trichoptera, order Ephemeroptera and followed by Odonata order families are reported in this paper. Water quality parameters i.e., pH, electrical conductivity, dissolved matter, dissolved oxygen, total suspended solids and nutrients were monitored in two different stations along the same segment of the river. The water quality assessment is based on: NIVA classification and the European Community directive on "quality of fresh waters supporting fish life". The conclusions from the chemical analyses are in good accordance to those obtained from biological parameters.